1997
DOI: 10.5694/j.1326-5377.1997.tb138784.x
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of longer consultations in Australian general practice

Abstract: ObjectiveTo assess the association between general practitioner (GP) billing for “longer” consultations, patient factors linked with health care need, and other consultation characteristics. DesignRetrospective analysis of data from Medicare (1984‐1992), Australian Morbidity and Treatment Survey (1990‐1991) and Australian Capital Territory Record Linkage Study (1988‐1992). SettingAustralian general practice, 1984 (introduction of Medicare) to 1992. Main outcome measuresConsultations billed as longer (< 20 or >… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
7
1

Year Published

1999
1999
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 1 publication
2
7
1
Order By: Relevance
“…This was more likely to occur in consultations of 20 or more minutes' duration (level C or above in the current descriptors or band 4 upwards in the proposed MSRTF descriptors). The ratio of standard to longer consultations in our study contrasts with national data (ratio of consultations with patients with a chronic disease diagnosis billed as standard [6-20 minutes] to those billed as longer [;;;.20 minutes] was closer to 16:1 in 1990-1991, 3 and not significantly different from the ratio for the whole population").…”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…This was more likely to occur in consultations of 20 or more minutes' duration (level C or above in the current descriptors or band 4 upwards in the proposed MSRTF descriptors). The ratio of standard to longer consultations in our study contrasts with national data (ratio of consultations with patients with a chronic disease diagnosis billed as standard [6-20 minutes] to those billed as longer [;;;.20 minutes] was closer to 16:1 in 1990-1991, 3 and not significantly different from the ratio for the whole population").…”
Section: Discussioncontrasting
confidence: 99%
“…Consequently, there was a greater proportion of longer consultations than national data would predict. 3…”
Section: Discussionmentioning
confidence: 99%
“…22 The HIC data showed that young women tended to see lessqualified practitioners, to see a greater number of different practitioners and to have fewer long consultations than older women. These findings are consistent with other Australian studies that have examined length of consultation 23 and use of multiple providers 24 in smaller samples. Lack of continuity of care among young women may reflect dissatisfaction with providers 22,24 or may be the result of the greater geographical mobility of these women.…”
Section: Discussionsupporting
confidence: 89%
“…A comparison of self-report and HIC records showed that record linkage provided accurate and economical measurement of health service use. 4 Several studies have been based on the linked records for these 521 persons concluding that a prospective longitudinal study was needed to explore the reasons why people see multiple general practitioners (GPs), 5 to determine whether longer consultations are accessed by those who need them most 6 and to investigate the relationship between patient need and health care supply and demand. 7 They also concluded that the population consent rates to such linkage remained to be established.…”
mentioning
confidence: 99%